2012
DOI: 10.1104/pp.111.192872
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast HMT1 Lowers Seed Cadmium through Phytochelatin-Dependent Vacuolar Sequestration in Arabidopsis    

Abstract: Much of our dietary uptake of heavy metals is through the consumption of plants. A long-sought strategy to reduce chronic exposure to heavy metals is to develop plant varieties with reduced accumulation in edible tissues. Here, we describe that the fission yeast (Schizosaccharomyces pombe) phytochelatin (PC)-cadmium (Cd) transporter SpHMT1 produced in Arabidopsis (Arabidopsis thaliana) was localized to tonoplast, and enhanced tolerance to and accumulation of Cd 2+ , copper, arsenic, and zinc. The action of SpH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…While protein phosphorylation has been shown to prompt PCS synthesis during GSH production , there are no known reports of protein phosphatases involved in PC regulation. Huang et al (2012) reported that Cd tolerance and accumulation failed when GSH and PC synthesis was blocked by L-buthionine sulfoximine, and also when PC synthesis was blocked in the PCS-deficient cad1-3 mutant.…”
Section: Phytochelatinsmentioning
confidence: 98%
“…While protein phosphorylation has been shown to prompt PCS synthesis during GSH production , there are no known reports of protein phosphatases involved in PC regulation. Huang et al (2012) reported that Cd tolerance and accumulation failed when GSH and PC synthesis was blocked by L-buthionine sulfoximine, and also when PC synthesis was blocked in the PCS-deficient cad1-3 mutant.…”
Section: Phytochelatinsmentioning
confidence: 98%
“…In plants, PCs can confer tolerance to heavy metal, as indicated by numerous recent studies, including Cd tolerance in B. juncea (Mohamed et al 2012), Populus nigra (Iori et al 2012), Oenothera odorata (Son et al 2012), T. aestivum (Hentz et al 2012), and Linum usitatissimum (Najmanova et al 2012); As tolerance in Nicotiana tabacum (Shukla et al 2012) and Arabidopsis thaliana (Huang et al 2012); Zn and Cu tolerance in Arabidopsis thaliana (Huang et al 2012); and Mn tolerance in Vitis vinifera (Yao et al 2012). Glutathione conjugates metals by forming PCs, which can be translocated.…”
Section: Toxic Metals/metalloidsmentioning
confidence: 99%
“…Similar to the above assays, root tissues (1.0 g) were collected from B. napus at seedling and flowering stages and from Arabidopsis (0.5 g) seedlings and used to isolate intact protoplasts and vacuoles as described by Robert et al (2007), with minor modifications as outlined in Huang et al (2012) and Han et al (2015b). The purified protoplasts were divided into two equal aliquots, with one of them used for isolation of vacuoles.…”
Section: Acc Treatmentmentioning
confidence: 99%